Bilateral aberrant origin of the inferior thyroid artery from the common carotid artery. - Mariolis-Sapsakos, Theodoros; Kalles, Vasileios; Papapanagiotou, Ioannis; Bonatsos, Vasileios; Orfanos, Nikolaos; Kaklamanos, Ioannis G; Manolis, Evangelos (Surg Radiol Anat, 2014)
The thyroid gland is mainly supplied by the superior and inferior thyroid arteries, with the latter being its principal arterial supply in adults. The inferior thyroid artery usually arises from the thyrocervical trunk, and less frequently from the subclavian artery. Rarely, it may originate from the vertebral artery or the common carotid artery. In the present report, we describe a unique case of a 56-year-old patient, undergoing total thyroidectomy and level VI lymph node dissection for papillary thyroid carcinoma, with aberrant origin of both inferior thyroid arteries from the common carotid arteries.
Keywords: Carcinoma; Carcinoma, Papillary; Carotid Artery, Common; Humans; Male; Middle Aged; Thyroid Cancer, Papillary; Thyroid Gland; Thyroid Neoplasms; Thyroidectomy